2011
DOI: 10.2527/jas.2009-2514
|View full text |Cite
|
Sign up to set email alerts
|

Feed efficiency differences and reranking in beef steers fed grower and finisher diets1

Abstract: This 3-yr study used 490 steers to determine whether feedlot steers changed their feed efficiency (FE) ranking when fed a grower diet, then a finisher diet. The steers were crossbreds and were between 5 to 7 mo of age. There were 2 feeding periods each year. Within each year, approximately 90 steers had their diet switched from a grower to a finisher diet (feed-swap group), whereas another 90 steers were fed either the grower (grower-fed group) or the finisher (finisher-fed group) diet throughout the feeding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
93
6
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 21 publications
16
93
6
1
Order By: Relevance
“…However, a higher correlation was observed in 2012 (r p 00.55, P 00.02) than 2013 (r p 00.13, P 0 0.51) indicating re-ranking for the trait when growing heifers were fed a high-forage diet under drylot conditions compared with pregnant heifers during summer grazing. Similar re-ranking has been observed by Kelly et al (2010a,b) and Durunna et al (2011) for heifers and steers on high-forage grower diets and higher-grain finishing diets. Few studies have reported the effect of post-weaning RFI classification in heifers on grazed forage intake in first-and higher parity cows.…”
Section: Resultssupporting
confidence: 69%
“…However, a higher correlation was observed in 2012 (r p 00.55, P 00.02) than 2013 (r p 00.13, P 0 0.51) indicating re-ranking for the trait when growing heifers were fed a high-forage diet under drylot conditions compared with pregnant heifers during summer grazing. Similar re-ranking has been observed by Kelly et al (2010a,b) and Durunna et al (2011) for heifers and steers on high-forage grower diets and higher-grain finishing diets. Few studies have reported the effect of post-weaning RFI classification in heifers on grazed forage intake in first-and higher parity cows.…”
Section: Resultssupporting
confidence: 69%
“…It is important to realize that RFI value of a given livestock is not as such a fixed value, and could vary depending upon models used and precision of data collection. Supporting evidence have been reported earlier [12] where more than half steers tested changed their RFI estimate by more than 0.5 standard deviations or 0.20 kg DM/d when measured on grower and finisher diets sequentially.…”
Section: Sorting Out the Heifers Into Rfi Groupssupporting
confidence: 60%
“…of RFI (range of 0.71 to 0.97 v. 0.61 to 0.88) compared with those using high-energy grain-based diets (Nkrumah et al, 2007;Lancaster et al, 2008 and2009b). However, Durunna et al (2011) found that the s.d. of RFI measured in the same cohort of steers fed a low-energy diet during the growing phase was lower than when RFI was measured using a high-energy diet during the finishing phase.…”
Section: Discussioncontrasting
confidence: 39%
“…In beef heifers, Kelly et al (2010b) estimated a moderate to high repeatability for RFI (r 5 0.62), calculated during growing and finishing periods when fed the same diet, indoors. Second, differences in the diets employed between the two measurement periods, that is, ensiled grass herbage plus supplementary concentrates v. grazed grass herbage, may be a factor as feed efficiency ranking can be affected by diet type (Durunna et al, 2011). In steers, Clarke et al (2009) reported a correlation of 0.30 between intake of grazed herbage determined using n-alkanes and subsequent individual intake of grass silage (weighed in and out) following housing 3 months later.…”
Section: Discussionmentioning
confidence: 99%